Differences in the What’s My M3? test between pre- and postmenopausal women - Carranza-Lira, Sebastián; Pablo-Cruz, Edith (Menopause Review/Przegląd Menopauzalny, 2017)
Aim of the study : To evaluate the differences in the What’s My M3 test between pre and postmenopausal women. Material and methods: Pre- and postmenopausal women who attended an endocrine gynaecology consultation were studied. In all them, the What’s My M3? test was applied. Descriptive statistics, central tendency and dispersion measures were used. Differences between groups were assessed with Mann Whitney U test, and Spearman correlation analysis was carried out for age and time since menopause with the What's My M3? score. Results: A total of 404 patients, aged 45 to 55 years, were surveyed. Women with previous diagnosis of depressive disorder, antidepressant use, history of hysterectomy with or without bilateral salpingo-oophorectomy were excluded. Finally 202 premenopausal and 164 postmenopausal were studied. A score in the What’s My M3? test ≥ 33 was considered as abnormal. Postmenopausal women had a higher score in the test than premenopausal women, 15 (0-69) and 6 (0-42) respectively (p < 0.001). In the sub-analysis of the What’s My M3? test, also the postmenopausal women had statistically significant greater score in depression, anxiety, bipolar disorder, obsessive-compulsive disorder, and post-traumatic stress disorder. It was found that when older, the women had a higher score (p < 0.001), (Spearman’s Rho, p < 0.005). Conclusions : Postmenopausal women had higher score in the What’s My M3? test than premenopausal women.